THE PEOPLE’S ADAPTATION TOWARDS THE NEW NORMAL LIFESTYLE DURING THE COVID-19 PANDEMIC IN NONTHABURI PROVINCE - Kruamek, Soracha; Kulprasutidilok, Akua; Ngamsakoo, Rujirapha (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
This research aimed to study people’s adaptation towards the New Normal lifestyle during the Covid-19 pandemic on the aspects of the economy, health, society and environment, IT usage, and education. The research utilized a Quantitative method. 448 households in Nonthaburi were multi-randomly selected to answer the questionnaires. The obtained data were analyzed by percentage and frequency. The results: In economic adaptation, 87.28% of the households did not create new occupations, 47.32% were affected in business operations, 80.11% got self-improvement by online learning, 87.05% cooked by themselves, 83.93% had a plan about money, and 62.50% had a plan about occupation. In health adaptation, more than 80% of the households always ate freshly cooked food, wore masks, and washed their hands with water and soap or alcohol gel. In social adaptation, 71.87% of the households participated in family activities whereas 50.45% participated in community activities decreasingly. In information technology adaptation, 47.10 of the households had self-learning about the use of communication devices. In education adaptation, 42.41 of the households never hired tutors for their children, and 21.88% managed family members’ time to teach or care for children.